Dispersion Characteristics and Aggregation in Titanate Nanowire Colloids. Issue 4 (24th February 2014) - Horváth, Endre; Grebikova, Lucie; Maroni, Plinio; Szabó, Tamás; Magrez, Arnaud; Forró, László; Szilagyi, Istvan
Abstract Titanate nanowires (TiONWs) are synthesized through the hydrothermal method and characterized in acidic aqueous dispersions by using electrophoresis, dynamic light scattering, and atomic force microscopy. The TiONWs have a rodlike shape with an average length of about 600 nm and a thickness of 35 nm. They are positively charged under the conditions used. Their surface charge properties and aggregation are investigated in the presence of oppositely charged poly(styrene sulfonate) (PSS) polyelectrolyte. Charge neutralization followed by a subsequent charge reversal process is observed, which is attributed to the adsorption of PSS. The colloids are unstable near the charge neutralization point and stable at lower and higher PSS doses, in good qualitative agreement with the theory developed by Derjaguin, Landau, Verwey, and Overbeek (DLVO). The nanowires prefer to align along the walls, leading to "spaghetti‐like" oriented aggregates. The aggregation processes of bare and PSS‐coated TiONWs are monitored at different concentrations of an inert electrolyte; slow aggregation is found at low salt levels, whereas aggregation is rapid beyond the critical coagulation concentration, as predicted by the DLVO theory, which describes the colloid stability of the TiONWs adequately in all the systems investigated. Coating of the nanowires with the polyelectrolyte leads to a critical coagulation concentration 75 times higher than that of the bare titanates, indicating the enormous stabilizing effect of PSS.